The Influence of Proximate Composition of Cow Dung on the Rate and Volume of Biogas Generation in Maiduguri, North Eastern Nigeria - I., Yerima; Ngulde, Y.M.; Mustapha, Abubakar; Ngala, A.L. (International Journal of Environment, Agriculture and Biotechnology, 2019)
This research investigates the Cow dung, Cow pats or Cow pies as a waste product of Cattle which constitute undigested residue of plant material and excreted by the animal as a waste. One dung cake made by hand of an average size gives 2100 kj of energy. The organic waste can be a source of renewable energy for rural areas especially in developing countries like Nigeria provided the material is subjected to anaerobic digestion to produce biogas as a means of waste disposal and alternative source of energy. Before this initiative of digesting Cow dung, the waste material is used as a direct fuel in clay stoves or three stone stoves and traditional fertilizer among peasant farmers in Nigeria and Asian countries. However, when discovered as a cheap, reliable and safe source of domestic fuel, energy experts and consumers thought of commercializing and patenting the gas. The research was carried out in the Laboratory of the Department of Biological Sciences, University of Maiduguri, Nigeria, using the batch system digester with a capacity of0.612 m3 and 0.24 m3as gasholder. About 0.2773 m3 of gas was released daily to control the excess pressure imposed on the gas holder (size 24, tractor tube). Laboratory and field analysis of the cow dung were carried out, followed by daily records of the volume of gas generated using ruler to measure and estimate the volume of the gas in cubic meter using the standard formula for measuring a cylinder (3.14 x r2 x h). The result of this research shows that the gas generated was methane due to combustion in combination with Carbon dioxide (CO2) due to non-combustion, Hydrogen Sulphide (H2S) due to rotten egg smell and water vapor. The daily volume of biogas generated was 0.27915 m3 on the average, with a maximum daily record of 0.5165 m3before declining after 73 days of the experiment and a cumulative volume of 77.62 m3in 52 days of methane production. The sustainability of cooking trial utilized an overall volume of 1.17 m3of the methane gas in 1hr to cook 1.5 kg of rice with ingredients and 0.553 m3in 1:35 hrs.to boil 20 liters of water. The digestion process was done in an airtight drum of 0.612 m3capacity as the digester.